Frequency scaling of rain attenuation - Ahmad, Sahadah (2007)
The most fundamental obstacle encountered in designing communication system at millimeter waves is attenuation due to rain especially at frequencies above 10GHz. Rain attenuation, however, increases approximately as the square of frequency. Rain attenuation will give greater impact on the satellite and terrestrial communication systems. It is therefore, very important to accurately predict rain attenuation for reliable incorporation into the design process based on the climate and geographical of the particular region. Frequency scaling of attenuation is the prediction of attenuation at a desired frequency from attenuation values at another frequency. The attenuation at the reference frequency is assumed to be known from prior measurements. Statistical frequency scaling is the use of statistics available from prior measurements at a base frequency to predict attenuation statistics at a desired frequency. Many scaling models have been developed from theory, empirical data, various propagation experiments, or from both. This project will focus on the results of an in-depth study on frequency scaling of attenuation. The investigation will begin with a thorough examination of one year of measured data for 23 GHz, 26 GHz and 38 GHz. In addition to being useful by themselves, these results will be used to evaluate the accuracy of available scaling models. The data were the value of signal received in volts. Processing of raw data were done by using ‘C’ programming, followed by the identification of dry period and wet period. The conversion of unit from volts to dBm , dB and dB/km and classification for cumulative distribution function also use the ‘C’ programming. All calculations and plotting of graphs involved were done in Microsoft Excell. The result of the analysis shows that the existing frequency scaling models cannot accurately predict the measured attenuation in the range of 23 GHz to 38 GHz in Malaysian tropical region even though they were good predictor in desert and temperate climate. The measurements demonstrated that statistical frequency scaling could be used to predict average instantaneous frequency scaling. Statistical frequency scaling can facilitate the calculation of link power budgets for new systems operating at higher frequencies in tropical region.